Bidirectional Interactions With Humpback Whale Singer Using Concrete Sound Elements - Pénitot, Aline; Schwarz, Diemo; Nguyen Hong Duc, Paul; Cazau, Dorian; Adam, Olivier (Frontiers in Psychology, 2021)
We describe an art–science project called “Feral Interactions — the Answer of the Humpback Whale” inspired by humpback whale songs and interactions between individuals based on mutual influences, learning process, or ranking in the dominance hierarchy. The aim was to build new sounds that can be used to initiate acoustic interactions with these whales, not in a one-way direction, as playbacks do, but in real inter-species exchanges. Thus we investigated how the humpback whales generate sounds in order to better understand their abilities and limits. By carefully listening to their emitted vocalizations we also describe their acoustic features and temporal structure, in a scientific way and also with a musical approach as it is done with musique concrète, in order to specify the types and the morphologies of whale sounds. The idea is to highlight the most precise information to generate our own sounds that will be suggested to the whales. Based on the approach developed in musique concrète, similarities with the sounds produced by bassoon were identified, and then were processed to become “concrete sound elements”. This analysis also brought us to design a new music interface that allows us to create adapted musical phrases in real-time. With this approach, interactions will be possible in both directions, from and to whales.